Development of a literacy enhancement system based on IoT and web technologies: integration of ESP8266 and Laravel - Dosbayev, Zhandos; Tuleshov, Amandyk; Osmanov, Arshidin; Sadykova, Bibigul; Smailov, Nurzhigit; Sabibolda, Akezhan (Eastern-European Journal of Enterprise Technologies, 2025)
The object of research is the application of multimedia technologies to support literacy learning in the Kazakh language through interactive tools based on the integration of IoT and Web technologies. The problem addressed is the lack of effective, interactive tools for learning correct spelling and pronunciation in the Kazakh language adaptable to different user roles and levels. This study focuses on the development of a multimedia, interactive educational system aimed at enhancing literacy and promoting active language acquisition. To design aimed system in hardware side an ESP8266 microcontroller was used. 74HC165 shift registers, pull-up resistors are also installed on each button to ensure signal stability. A server side software solution built on the Laravel framework. Communication between the microcontroller and the server is established using the WebSocket protocol, a secure connection between the hardware device and the server is provided through the MAC address. The server runs in a Docker container using the Nginx and supports user roles such administrator, teacher, and student. The results obtained include a working prototype of learning system that allows users to complete tasks in five interactive modes. The results show that the integration of real-time hardware input with a flexible server-side architecture improves user engagement and learning personalization. The features of the solution are its real-time two-way communication via Websocket, role-based access, modular design in Docker, and support for Kazakh language content. The solution is intended at supporting educational institutions, kindergartens, and remote learning environments for learning letters and words, advancing digital education practices, and improving adaptable methods and technologies for the development of IoT based educational tools